Parenting Pattern of Orphan and Dhuafa Children in Building Religious Character - Agus Winarti; Livia Astuti (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2022)
Parenting is a method parents apply to provide children guidance, direction and care. Proper parenting will build a positive and personal child's character. This research aims to determine how to implement orphanage parenting in building the religious nature of orphans and the poor and the support and obstacles in building children's character at the Ar-Rifqi orphanage in Bandung. The research subjects were teachers/ustadz, caregivers and learning residents at the orphanage. Field research with a qualitative descriptive approach. Methods of data collection using observation, interviews, and documentation. Analysis techniques: data reduction, data presentation and conclusions. The research results are (1) Implementation of orphanage parenting in building the religious character of orphans and dhuafa by using democratic parenting. (2) Supporting factors are the background of foster children who are orphans and poor, in dire need of parental love, and loving foster parents (3) Inhibiting factors are inadequate learning facilities. These findings show that orphanages have played an active role in building the religious character of orphans and the poor. Therefore it is suggested that democratic parenting is studied more broadly and in-depth so that it can then be applied to other orphanages.